Implementasi Kebijakan Konflik Lahan Transmigrasi di Desa Gambut Jaya Kabupaten Muaro Jambi - Sarwani, Raden (Universitas Batanghari Jambi, 2025)
For the community, this conflict can result in loss of livelihoods, increased poverty rates, and divisions within the community. On the other hand, for the government, land conflicts can reduce the legitimacy and trust of the community in the authorities, especially if they are considered incapable of resolving problems fairly. Prolonged conflicts can also disrupt the investment climate, leading to development delays and slowing economic growth at the local level. Therefore, it is expected to see the extent to which the implementation of policies has been carried out by the local government regarding the transmigration land conflict in Gambut Jaya Village, and how to solve the problem for the welfare of the farming community. This research is a qualitative research, which involves the process of action to overcome problems by explaining the research object in detail and in depth. The goal is to achieve a more comprehensive understanding and make generalizations about the variables that influence a phenomenon or social reality. Implementation of Local Government Policy on Transmigration Land Conflicts in Gambut Jaya Village: Communication. All forms of efforts have been made, both formally and informally. Formally, the community has tried to the Local Government, even discussing it in the Regent's meeting room. At the beginning, it was concluded that an integrated team had been formed to measure the promised land, but because it was hampered by the regional election process, the promise was forgotten again, so that the transmigrant community returned to empty hopes. If formal efforts were unsuccessful, in the end the transmigrant community took non-formal routes, namely by taking action. Various levels of government have taken action, both from the Regent, Governor, and ATR/BPN Jambi, but it did not produce any results at all, all that was obtained was promises that were not fulfilled